2018
DOI: 10.18632/oncotarget.25215
|View full text |Cite
|
Sign up to set email alerts
|

Italian real life experience with ibrutinib: results of a large observational study on 77 relapsed/refractory mantle cell lymphoma

Abstract: Although sometimes presenting as an indolent lymphoma, mantle cell lymphoma (MCL) is an aggressive disease, hardly curable with standard chemo-immunotherapy. Current approaches have greatly improved patients’ outcomes, nevertheless the disease is still characterized by high relapse rates. Before approval by EMA, Italian patients with relapsed/refractory MCL were granted ibrutinib early access through a Named Patient Program (NPP).An observational, retrospective, multicenter study was conducted. Seventy-seven h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 19 publications
2
28
2
Order By: Relevance
“…followed 111 patients with MCL treated with single‐agent ibrutinib 560 mg daily, the median age of patients was 68 years, the median duration on ibrutinib was 8·3 months and the median OS was 22·5 months (95% CI 13·7–NR) 10 . In other retrospective, observational studies, a median OS of 16 months and 22 months were reported by Broccoli et al 2 . and Epperla et al 16 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…followed 111 patients with MCL treated with single‐agent ibrutinib 560 mg daily, the median age of patients was 68 years, the median duration on ibrutinib was 8·3 months and the median OS was 22·5 months (95% CI 13·7–NR) 10 . In other retrospective, observational studies, a median OS of 16 months and 22 months were reported by Broccoli et al 2 . and Epperla et al 16 .…”
Section: Discussionmentioning
confidence: 92%
“…MCL is usually diagnosed as a late‐stage disease that often involves the gastrointestinal tract and bone marrow 1 . Although front‐line therapy can achieve disease control, relapses are expected and most patients will die from their disease 2 . In the USA, there were approximately 70 800 new cases of NHL in 2014, with patients with MCL representing 3–6% of all new cases 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Following removal of duplicate papers, 901 papers remained; of these 805 articles were removed after the titles and abstracts were screened, leaving 66 articles for full screening. From these papers, 16 articles met all the inclusion criteria, and were taken forward for qualitative synthesis ( Table 2 [ 13 , 23 , 24 , 32 , 54 , 55 , 56 , 57 , 58 , 59 61 , 63 , 64 , 65 , 67 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Our study identified five different treatment regimens which had been examined within the criteria of this review: elderly/unfit patients after the introduction of ibrutinib in 2012. The three most frequently studied treatments were R‐CHOP (eight studies [ 13 , 23 , 33 , 55 , 56 , 60 , 61 , 65 ]), ibrutinib (five studies [ 24 , 54 , 59 , 63 ]) and bendamustine (three studies [ 13 , 33 , 60 ]). We found that treatment outcomes in patients treated with R‐CHOP were not inferior to those with ibrutinib or BR.…”
Section: Discussionmentioning
confidence: 99%
“…Our series mainly included MCL patients with advanced disease, with more than one extranodal site affected, who had been moderately pre-treated (77% of patients had received 1–2 prior lines of therapy) compared with the patients receiving 2 prior lines of therapy or less in phase II SPARK (52.5%) and phase III RAY (68%) studies [ 8 , 9 ] and other real-world cohorts including more heavily pre-treated patients (ranging from 55 to 70%) [ 11 , 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%